The Last (Koy-Yukon) Interglaciation in the Northern Yukon: Evidence from Unit 4 at Ch’ijee’s Bluff, Bluefish Basin - Matthews, John; Schweger, Charles; Janssens, Jan (Géographie physique et Quaternaire, 1990)
ABSTRACTThe effects of predicted anthropogenic warming can be assessed in part by documenting responses to past warming events. One of the most pronounced warmings was the last interglaciation - stage 5 of the marine isotope record. A large multinational and multidisciplinary project (CELIA) was launched recently in order to gain detailed knowledge of the climate during stage 5. Several key exposures were identified by CELIA; one of them is Ch'ijee's Bluff on the Porcupine River, northern Yukon. Pollen, plant and insect macrofossils and stratigraphie evidence from Ch'ijee's Bluff show that the part of Ch'ijee's Unit 4 that is above and younger than Old Crow tephra (OCt) was deposited during an interval of climate warmer than present. When OCt was dated at 85 ka BP, the subsequent warming interval was presumed to be correlative with the early part of marine isotope stage 3. New dates on OCt show it to be 140-150 ka BP, and this means that the warm interval discussed here is more likely of stage 5 than stage 3 age. We apply the informal epithet, "Koy-Yukon interglaciation", to it and compare the Ch'ijee's Bluff Unit 4 sequence with other east Beringian sites that contain both Old Crow tephra and putative interglacial deposits.